ChemInform Abstract: Valence State Driven Site Preference in the Quaternary Compound Ca5MgAgGe5: An Electron‐Deficient Phase with Optimized Bonding. Issue 27 (8th July 2014) - Ponou, Simeon; Lidin, Sven; Zhang, Yuemei; Miller, Gordon J.
Abstract Ca5Mg0.95Ag1.05Ge5 is synthesized by solid state reaction of the elements in the atomic ratio Ca:Mg:Ag:Ge = 3:1:1:2 (Nb/Ta tube, Ar atmosphere, 870 °C, 5 d).